2012
DOI: 10.1073/pnas.1118048109
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic disorder modulates protein self-assembly and aggregation

Abstract: Protein molecules have evolved to adopt distinctive and welldefined functional and soluble states under physiological conditions. In some circumstances, however, proteins can self-assemble into fibrillar aggregates designated as amyloid fibrils. In vivo these processes are normally associated with severe pathological conditions but can sometimes have functional relevance. One such example is the hydrophobins, whose aggregation at air-water interfaces serves to create robust protein coats that help fungal spore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 42 publications
8
93
0
Order By: Relevance
“…As a result, amino acid sequences, in the absence of any selection, are expected to devolve rapidly into disorder. Although there are many good reasons to think that disorder can play an important role in proteins (20,52,53), firmly establishing a functional role for disorder has been experimentally difficult. As a conditionally disordered protein, HdeA opens up a unique approach to dissecting the contribution of disorder to protein function.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, amino acid sequences, in the absence of any selection, are expected to devolve rapidly into disorder. Although there are many good reasons to think that disorder can play an important role in proteins (20,52,53), firmly establishing a functional role for disorder has been experimentally difficult. As a conditionally disordered protein, HdeA opens up a unique approach to dissecting the contribution of disorder to protein function.…”
Section: Discussionmentioning
confidence: 99%
“…Long polypeptide chains of biological molecules, similar to polymers, are intrinsically designed to fold to form globular structures to decrease surface energy by increasing molecular bonds 40 . Such self-assembled macromolecular complexes formed from long-chained polymers share similar features of lamellar extensions, radial growth and so on, generally termed as a spherulite 41 .…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Schulz et al [65] this change in conformational behaviour can strongly influence the potential application of these proteins, specifically finding that EAS (a class-I hydrophobin) induced the formation of hydroxyapatite at water-hexane interface, whereas HFBII did not, which can be explained by the larger conformational change exhibited by EAS at the interface and in the presence of Ca 2+ and HPO 4 − ions. Simulation of EAS [66] using a multiscale model also showed that its conformational change is responsible for the aggregation of these proteins into fibrils, underlining the importance of accurately representing conformational change in these proteins. Going beyond hydrophobins, Euston has also compared atomistic and coarse-grain models for the simulation of proteins at fluid interfaces [67], finding that CG models gave results similar to atomistic models, although the CG model used underestimated the penetration of the protein (Barley LTP) into the oil phase.…”
Section: Proteinsmentioning
confidence: 99%